Continuous auditing : theory and application - Chan, David, 1960-; Chiu, Victoria; Vasarhelyi, Miklos A. (Rutgers studies in acounting analytics, 2018)
Continuous auditing is a novel emerging technology in academia and practice. The concept of continuous auditing was conceived over two decades ago in academia and we are now at a junction where the auditing profession recognizes the implement-ability and value of a continuous audit. The book's purpose is twofold. First, the book aims to provide academics and practitioners with a compilation of select continuous auditing design science research that can be used as a springboard to future research and development. Second, the book aims to provide readers with an understand of the underlying theoretical concepts of a continuous audit, ideas on how continuous audit can be applied in practice, and what has and has not worked in research.